Identity Management Reform and Fraud Prevention in the Nigerian Banking Industry - Ikeobi, Nneka Rosemary (PhD); Ayeni, Akintunde Olawande (PhD) (International Journal of Engineering and Management Research, 2021)
This paper assesses the effect of identity management reform, namely the Bank verification number (BVN) policy on fraud prevention in the Nigerian banking industry. Using secondary data obtained from annual reports of Nigerian Deposit Insurance Corporation (NDIC) from 2011 to 2018, the study employed descriptive method to analyze trend in fraud variables before and after introduction of the policy and independent t-test to test the hypotheses in the study. Findings revealed that there was an initial decrease in number of staff involved and total amount involved in fraud in the two years following BVN introduction, but which showed increases thereafter. A similar trend was revealed in various fraud types with internet banking fraud showing significant increases in frequency of cases. The results from the t-tests revealed that the BVN policy had no significant impact on fraud prevention within the period under study. It was recommended that the banking public be educated on the different types of fraud and how to protect their personal details from getting into wrong hands. There is also the need to beef up security by improving on protocols required to carry out bank transactions particularly in the area of internet banking. It was also suggested that all bank account numbers be linked to the National Identity Number (NIN) immediately in line with proposals made by the Federal Government on identity management.